Remote Work and Organisational Innovations: Post Covid-19 insights - Maciej P. KOCZERGA (Communications of International Proceedings, 2023)
The COVID-19 pandemic and its associated restrictions have had a significant impact on all aspects of human activity, particularly on the business operations of companies. The sudden transition to remote work has caused significant disruptions for employees, with initial reports indicating a negative impact on innovation activities within enterprises. These observations acted as a catalyst to explain this particular phenomenon. While much of the literature on remote work focuses on individual effects, such as e.g. employee safety and work-life balance, few studies have explored the impact on organisations as a whole. This conceptual work draws on a critical review of existing literature to formulate conclusions about the impact of remote work on innovative activities in organisations. The study findings suggest that the decline in innovation within organizations may be attributed to changes in the organization of work brought about by remote work arrangements impacting both organisational objectives and climate for innovation. Based on the findings, it can be inferred that innovative activities can be performed while working remotely or in a hybrid situation, subject to specific conditions being met, such as the development of climate for innovation and the utilization of suitable digital solutions. Achieving these conditions may require significant organizational adjustments and changes in management practices, which may face resistance from some organisational stakeholders. The conclusions drawn from this study have the potential to provide significant insights for future endeavours aimed at preventing a potential downturn in innovativeness among organizations, especially during their shift towards hybrid work models.
Keywords: remote working; hybrid working; innovation